Impact of Biomass Burning and Vertical Mixing of Residual‐Layer Aged Plumes on Ozone in the Yangtze River Delta, China: A Tethered‐Balloon Measurement and Modeling Study of a Multiday Ozone Episode. Issue 20 (30th October 2018) - Xu, Zhengning; Huang, Xin; Nie, Wei; Shen, Yicheng; Zheng, Longfei; Xie, Yuning; Wang, Tianyi; Ding, Ke; Liu, Lixia; Zhou, Derong; Qi, Ximeng; Ding, Aijun
Abstract: Ozone (O3 ) is one of the most important trace gases in the troposphere because of its impact on human health, crop yield, climate change, and atmospheric oxidizing capacity. In recent years, China has suffered from deleterious O3 pollution in many regions, especially in eastern China during summer. However, understanding the causes of high O3 pollution episodes is still limited because existing measurements were mainly conducted at the surface level. In this study, we conducted an intensive tethered‐balloon measurement at the Station for Observing Regional Processes of the Earth System in the Yangtze River Delta during a multiday O3 episode in mid‐June 2014, with the highest hourly surface O3 record (142 ppbv) at the station in 2014. By integrating available ground‐based, remote sensing and aircraft measurement data together with chemical transport modeling and Lagrangian dispersion modeling, we carried out a comprehensive analysis of the main source and formation mechanism for two typical days during the multiday O3 episode. On 11 June, agricultural straw burning in the north significantly enhanced O3 concentration (40–50 ppbv) above the planetary boundary layer (PBL) over Nanjing and further influenced the downwind surface O3 in the following days. On 14 June, regional photochemically aged air masses from city clusters in the Yangtze River Delta substantially influenced early morning ground O3 concentrations by vertical mixing from the residual layer and contributed to PBL daytime O3 buildup. This study provides a clear picture of the transport and mixing of O3 and relevant pollutants in the PBL from different sources and highlights the significance of regional emission control in the mitigation of photochemical pollution in eastern China. Plain Language Summary: Ozone pollution is one the important air quality concerns in China, especially in early summer. The causes of high ozone pollution events are poorly understood because of less information about the vertical profiles. Here we conducted intensive measurement of ozone with a tethered‐balloon platform in Nanjing, a city in the western Yangtze River Delta, China during a multi‐day ozone episode in mid‐June 2014. Highest hourly surface ozone record (142 ppbv) in 2014 was observed at that day. Various measurement data from ground‐based, remote sensing and aircraft platforms during the same period, and numerical modeling with two different models were conducted to understand the mechanisms and causes during this event.We found that agricultural straw burning has strong impact on ozone concentrations in the free troposphere of eastern China and ground surface in the downwind area. The vertical mixing of aged "city" plumes in the residual‐layer had important influence on the fast increase of surface ozone in the morning and the daytime buildup.Our study gives a clearer picture about the transport and mixing of ozone and relevant pollutants in the boundary layer from different sources, and highlights the significance of regional emission control in mitigation of photochemical pollution in eastern China. Key Points: Diurnal variation of boundary layer ozone was measured using tethered‐balloon platform for a multiday ozone episode in Nanjing, east China Agricultural biomass burning influenced ozone concentration in the free troposphere and within boundary layer in the downwind region Vertical mixing of aged urban plumes from the residual layer significantly influences morning surface ozone and daytime ozone buildup